Effects of a Coordinative Ability Training Program on Adolescents’ Cognitive Functioning - Latino, Francesca; Cataldi, Stefania; Fischetti, Francesco (Frontiers in Psychology, 2021)
The purpose of this randomized controlled study was to investigate the effects of a 12-week coordinative ability training program on adolescents’ cognitive functioning, using evaluation tests of visuospatial perception, attention, and working memory. We randomly assigned 60 public school students (14-15 years) to either an experimental coordinative abilities training (~40 minutes twice/week) group (n = 30) or a control group (n = 30) who received general psycho-physical wellness training (~ 40 min., twice a week). At baseline and after training we used two standardized motor tests and a single cognitive measure (Corsi’s Block-tapping test) to assess students’ visuospatial perception, attention, and working memory. We found a significant Time x Group interaction for the Throwing and Catching Test and Corsi's Block-Tapping test, reflecting a meaningful experimental group improvement (p < 0.001), and there were no significant pre-post changes found in the control group. Thus, a 12-week program of coordinative abilities was able to improve not only coordination skills but aspects of cognitive functioning relevant to academic achievement.